Collective Knowledge Formation as a Prerequisite for Managing Public Sector Effectiveness - Harri Laihonen; Lotta-Maria Sinervo; Anna-Aurora Kork (European Conference on Knowledge Management, 2026)
Effectiveness is a central ambition in public governance, yet public organizations continue to struggle with how it should be defined, assessed, and managed. Prior research has identified key mechanisms through which public sector organizations attempt to render effectiveness manageable, including goal setting, policy‑making, resource allocation, impact assessment, and knowledge management. However, while these mechanisms help explain organizational activities, less attention has been paid to how shared understanding of effectiveness emerges in complex, multi‑actor public sector environments. This conceptual article contributes to knowledge management research by reframing public management mechanisms through the lens of collective knowledge formation. We conceptualize public sector effectiveness as a continuous knowledge process in which diverse actors, policymakers, managers, professionals, and other stakeholders, jointly construct what effectiveness means, determine what constitutes relevant and credible knowledge, and translate this understanding into coordinated action. Drawing on a knowledge formation perspective, the article develops a conceptual framework that explains how public management mechanisms operate as knowledge processes rather than merely as managerial procedures. We argue that public sector effectiveness cannot be managed without dialogical knowledge creation across multiple governance levels. Through collective knowledge formation, abstract policy goals are interpreted and transformed into shared understandings that guide organizational action. This shared knowledge provides the foundation for managing public sector effectiveness. By integrating public management mechanisms with concepts from knowledge management, the article foregrounds the epistemic foundations of managing public sector effectiveness.